Performance Evaluation of The Regional Disaster Management Agency in Preventing Forest and Land Fires in The Meranti Islands Regency - Syaprianto, Syaprianto; Wardana, Data; Erfina, Erfina (UIR Press, 2024)
The government must prevent forest and land fires so that they do not continue to occur. Forest and land fires in the Meranti Islands Regency continue to occur. This study uses the evaluation theory according to Willian N Dunn to determine the Performance of the Regional Disaster Management Agency in Preventing Forest and Land Fires in the Meranti Islands Regency. The research method used in this research is qualitative, by interviewing direct and in-depth informants who know the problems being studied best. The study results show that the Regional Disaster Management Agency in Preventing Forest and Land Fires in the Meranti Islands Regency has worked according to its duties and functions. However, its performance has yet to be maximized. The occurrence of forest and land fires in the Meranti Islands Regency evidences this.